Energy Release Analysis of a Severe Rockburst in a Headrace Tunnel Crossing a Tectonic Stress Zone - H. M. Tian; W. Z. Chen; C. S. Ma; D. S. Yang; X. J. Tan (Shock and Vibration)
When tunneling in a hard and brittle rock mass within a tectonic stress zone, dynamic failure of rock mass-rockburst may occur. Considering the occurrence of rockburst is generally induced by a sudden release of storage elastic energy, a numerical analysis based on the geotechnical conditions of the headrace tunnels of the Neelum–Jhelum hydroelectric project was carried out to investigate the variations of the storage elastic energy of surrounding rock mass during excavation in the tectonic stress zone. As expected, the numerical results show that the storage elastic energy concentration zones is elliptical around the tunnel due to the influence of the tectonic stress field and that the long axis of the ellipse is perpendicular to the orientation of the maximum principal stress of the tectonic stress. Furthermore, the calculated storage energy concentration zone is consistent with the locations of blasting overbreak in the tunnel. Rockburst predictions were carried out using the strength-stress ratio and energy criteria to identify the applicability of the criteria in a tectonic stress zone. The comparisons between the predictions and the field observations show that the strength-stress ratio criteria based on the uniaxial tests do not consider the influence of the tectonic stress on the strength of the rock. These criteria overpredict the extent of the blasting pits in the tectonic stress zone. However, the energy criteria based on the energy conversion of unloading confining pressure tests are able to reflect the influence of the tectonic stress, and the prediction results are more close to the field observations.